Multi-dimensional Visualisation of Laboratory Findings and Functional Test Results for Analysing the Clinical Course of Disease in Medicine - Goldschmidt, A. J. W.; Luz, C. J.; Giere, W.; Lüdecke, R.; Jonas, D. (Methods of Information in Medicine, 1995)
The illustration of a patient’s history by a graphical primitive is discussed. Illustration technology is presented which simultaneously represents quantitative examination findings (e. g., laboratory values) and qualitative findings (e. g., from function diagnostics) by a single geometrical figure. Depending on the medical results, this figure takes on characteristic forms which can be identified as patterns typical for a specific disease. The procedure developed is integrated in a user interface which is implemented in the form of a computerized medical record for use on a pentop computer. This portable computer assists the physician during ward rounds, supplies additional, intelligence-based information, serves quality control, and streamlines working procedures making them more efficient.
Keywords: Pentop; Graphical User Interface; Graphical Data Representation; Electronic Medical Record